Microgrids for rural schools: An energy-education accord to curb societal challenges for sustainable rural developments - Abhi Chatterjee; Alan Brent; Ramesh Rayudu; Piyush Verma (International Journal of Renewable Energy Development, 2019)
Quality education and schools have a key role to play in the sustainable development of society. Unfortunately, many remote communities in developing countries fail to enjoy access to quality education due to a lack of electricity, thereby interrupting regular school services in the villages. The main objective of the paper contributes to understanding the importance of the energy-education accord, and aims to curb the social challenges prevailing in the villages. Specifically, the paper suggests a technical intervention by designing a hybrid renewable energy system for such schools. The approach is demonstrated through a case study with a load demand of approximately 4 kWh/d, comprising a class size of 40 students. A techno-economic evaluation of the energy system reveals the levelized cost of energy of the system at USD 0.22 per kWh, which may be affordable considering number of other aspects, outlined in this paper, to enable a larger uptake of such systems in developing countries. ©2019. CBIORE-IJRED. All rights reserved